Hydraulic constraints determine the distribution of heteromorphic leaves along plant vertical height - Yang, Xiao-Dong; Anwar, Elhamjan; Xu, Yi-Lu; Zhou, Jie; Sha, Long-Bin; Gong, Xue-Wei; Ali, Arshad; Gao, Yong-Chao; Liu, Yanju; Ge, Ping (Frontiers in Plant Science, 2022)
As an interesting and important trait of some drought tolerant species, heteromorphic leaves are distributed differentially along plant vertical heights. Yet, the underpinning mechanism for the formation of heteromorphic leaves remains unclear. Here, we hypothesize that heteromorphic leaves are caused by the hydraulic constraints, possibly due to the compensation of the changes in functional traits in response to water transport capacity or the reduction of ineffective water loss. In this study, differences in water transport capacity, morphological traits, anatomical structures and cellular water relations among three typical types of heteromorphic leaves (i.e., lanceolate, ovate, and broad-ovate) of Populus euphratica Oliv. (a dominant species of desert riparian forest in the Central and West Asia), and their relationships were analyzed in order to explore the forming mechanism of heteromorphic leaves. The results showed that the lanceolate, ovate, and broad-ovate leaves were distributed in the lower, intermediate and upper canopy positions of large trees, respectively. Morphological traits, anatomical structures, cellular water relations and water transport capacity significantly varied among three types of heteromorphic leaves (P < 0.01). Drought stress in broad-ovate leaves was significantly higher than that in ovate and lanceolate leaves (P < 0.01), while midday leaf water potential showed opposite pattern (P < 0.01). Water transport capacity has significant correlations with morphological traits, anatomical structures and cellular water relations (R2 ≥ 0.30; P < 0.01). Our results indicated that heteromorphic leaves were used as an important adaptive strategy for P. euphratica to alleviate the increase of hydraulic constraints along vertical heights.